2022
DOI: 10.1002/jcsm.13121
|View full text |Cite
|
Sign up to set email alerts
|

Activation of eIF4E‐binding‐protein‐1 rescues mTORC1‐induced sarcopenia by expanding lysosomal degradation capacity

Abstract: Background Chronic mTORC1 activation in skeletal muscle is linked with age‐associated loss of muscle mass and strength, known as sarcopenia. Genetic activation of mTORC1 by conditionally ablating mTORC1 upstream inhibitor TSC1 in skeletal muscle accelerates sarcopenia development in adult mice. Conversely, genetic suppression of mTORC1 downstream effectors of protein synthesis delays sarcopenia in natural aging mice. mTORC1 promotes protein synthesis by activating ribosomal protein S6 kinases (S6Ks) and inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This may be advantageous for developing therapeutic approaches that target FOXO3a independently of the IGF-1-PI3K-Akt pathway due to potential side effects associated with PI3k-Akt activation [46, 47]. In addition, over-activation of protein synthesis, which is a downstream target of IGF-1-PI3K-Akt, has recently been observed in aging-related skeletal muscle wasting [48, 49]. Strategies to further increase protein synthesis in geriatric muscle may worsen proteostatic stress [48].…”
Section: Discussionmentioning
confidence: 99%
“…This may be advantageous for developing therapeutic approaches that target FOXO3a independently of the IGF-1-PI3K-Akt pathway due to potential side effects associated with PI3k-Akt activation [46, 47]. In addition, over-activation of protein synthesis, which is a downstream target of IGF-1-PI3K-Akt, has recently been observed in aging-related skeletal muscle wasting [48, 49]. Strategies to further increase protein synthesis in geriatric muscle may worsen proteostatic stress [48].…”
Section: Discussionmentioning
confidence: 99%
“…1 Therefore, abundance of eIF4E is essential for translation of mRNAs coding for proteins that play critical roles in regulating cellular functions such as proliferation, malignant transformation, 27 mitochondrial dynamics, 8,9 learning and memory, 10–14 and aging. 15,16 Consistently, studies that increased or reduced eIF4E expression and/or its cellular inhibitors and activators demonstrated that non-physiologic activation of eIF4E significantly contributes to pathophysiology of many human disorders including cancer, 17,18 diabetes, 19,20 autism related learning deficits, 2123 Parkinson’s, 24 Huntington’s 25 and Alzheimer’s diseases 26 and play a causative role in fragile-X mental retardation syndrome. 27,28 These studies indicate that reducing eIF4E expression/activity may be beneficial for the management of an array of human disorders.…”
Section: Introductionmentioning
confidence: 90%
“…Skeletal muscle is one of the tissues with the highest challenges to protein quality control due to contraction-associated mechanical protein unfolding and oxidative damage. 19 - 23 In both Drosophila and mammals, 24 skeletal muscle aging is characterized by a prominent loss of protein quality control, 20 , 21 , 25 - 28 as indicated by the progressive accumulation of poly-ubiquitinated protein aggregates with aging and by the age-related increase in ubiquitinated proteins detected in detergent-insoluble fractions ( Figure 1A ). Although dysfunction of the autophagy-lysosome and ubiquitin-proteasome systems has been shown to contribute to loss of proteostasis in muscle with aging, 20 , 29 - 31 it is largely unknown whether other proteolytic systems contribute to the derangement of muscle proteostasis.…”
Section: Introductionmentioning
confidence: 99%